DEVELOPMENT OF A STUDENT WORKSHEET ON MEGIBUNG TRADITION MATERIAL BASED ON PROJECT-BASED LEARNING IN THE CULINARY ARTS VOCATIONAL EDUCATION STUDY PROGRAM - Sukerti, Ni Wayan; Marsiti, Cokorda Istri Raka (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
This research aims to describe the student responses to the developed Student Worksheets on Megibung Tradition material in the Balinese Culinary course. It employs a type of development research intended to develop Student Worksheets for Balinese Culinary courses. The subjects of this study were third-semester students of Culinary Arts Vocational Education FTK Undiksha. The selection of these subjects is based on the urgency of providing Balinese Culinary teaching materials, researchers’ role as lecturers, and research respondents. This research instrument is an assessment format consisting of aspects related to (1) material/concept, (2) construction, and (3) technical elements. The results showed that: (1) there are two stages in developing Student Worksheets, namely the preparation stage and the development stage. (2) A feasibility analysis indicated that the use of Student Worksheets with a project-based learning approach is suitable for learning and can enhance student creativity, specifically in the Balinese Culinary course for the ability to serve food with Megibung. (3) After making improvements based on expert validation, student response measurements were taken as users of this Student Worksheet. In general, the results of the student response questionnaire were summarized as follows: 75% of students rated this Student Worksheet as good, 10% gave a moderate response, and 10% gave a very good response.